1999
DOI: 10.1021/ja983949i
|View full text |Cite
|
Sign up to set email alerts
|

Highly Regio- and Stereocontrolled Synthesis of Vinyl Sulfides via Transition-Metal-Catalyzed Hydrothiolation of Alkynes with Thiols

Abstract: Regio- and stereoselectivity in the hydrothiolation of alkynes with thiols in the presence of a variety of transition-metal catalysts is investigated in detail. Among the catalysts employed, RhCl(PPh3)3 exhibits excellent catalytic ability toward the anti-Markovnikov addition of thiols (ArSH) to alkynes (RC⋮CH), which affords the corresponding vinylic sulfides (trans-RCHCHSAr) regio- and stereoselectively. The reaction may proceed by the formation of hydrorhodium sulfide species (H−[Rh]−SAr) and probably via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
143
0
6

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(152 citation statements)
references
References 32 publications
2
143
0
6
Order By: Relevance
“…87,88 Usigi et al found that treatment of diphenyl disulfide and terminal alkynes with gallium chloride affords (E)-1,2-diphenylthio-1-alkenes selectively (Scheme 40). 89 Alkenes can be transformed in a similar fashion, affording the trans adduct.…”
Section: Disulfidation Of Alkynes and Alkenesmentioning
confidence: 99%
“…87,88 Usigi et al found that treatment of diphenyl disulfide and terminal alkynes with gallium chloride affords (E)-1,2-diphenylthio-1-alkenes selectively (Scheme 40). 89 Alkenes can be transformed in a similar fashion, affording the trans adduct.…”
Section: Disulfidation Of Alkynes and Alkenesmentioning
confidence: 99%
“…Recently, we have developed a series of highly selective transition-metal-catalyzed reactions of organosulfur compounds with acetylenes [30][31][32][33], and therefore this prompted us to examine the construction of -conjugated system.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, changing the catalyst from palladium acetate to Wilkinson's catalyst (RhCl(PPh 3 ) 3 ) causes anti-Markovnikov addition of thiols to terminal alkynes with excellent stereoselectivity (syn-addition) (Scheme 2) [31]. The reaction may involve the oxidative addition of thiols to the catalyst generating HRh(SPh)Cl(PPh 3 ) 3 , followed by hydrorhodation of alkynes and reductive elimination of the product with recovery of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…As with the thiol-ene reaction, the thiol-yne reaction, in general, proceeds rapidly under a variety of experimental conditions selectively yielding the mono or bisaddition products. [24][25][26][27][28][29] In the case of the double addition products formed under radical conditions, the reaction of two equivalents of thiol with a terminal alkyne is itself a two-step process, Scheme 2. The first, slower, step (1) involves the regiospecific antiMarkovnikov-like addition of a thiyl radical across the CBC bond yielding the intermediate vinylic radical as a mixture of the cis and trans diastereoiosomers.…”
Section: Introductionmentioning
confidence: 99%